Recurrent IgG4‐related tubulointerstitial nephritis concurrent with chronic active antibody mediated rejection: A case report. Issue 7 (24th April 2018) - Chibbar, Rajni; Wright, Glenda R.; Dokouhaki, Pouneh; Dumanski, Sandi; Prasad, Bhanu; Mengel, Michael; Cornell, Lynn D.; Shoker, Ahmed
Abstract : IgG4‐related disease is a relatively newly described entity that can affect nearly any organ, including the kidneys, where it usually manifests as tubulointerstitial nephritis (IgG4‐TIN). The diagnosis can be suggested by characteristic histological features, including an inflammatory infiltrate with increased IgG4‐positive plasma cells associated with "storiform" fibrosis. Serum IgG4 is usually elevated. In the native kidney and other organs, there is typically a brisk response to treatment with immunosuppression. Recurrence of IgG4‐TIN after renal transplant has not been described in the literature. Here, we describe the first case of recurrent IgG4‐TIN in a young patient concomitant with chronic active antibody mediated rejection five years after kidney transplant. Recurrent IgG4‐TIN could be diagnosed by the characteristic histopathologic features and increased IgG4‐positive plasma cells. Despite maintenance immunosuppression, this disease may recur in the kidney allograft. Abstract : This case illustrates recurrence of IgG4‐related tubulointerstitial nephritis 5 years posttransplant in an allograft kidney concurrent with chronic active antibody‐mediated rejection.